Poaceae and Fabaceae of meadows of Poltava region and their protein value - Orlova, Larysa; Vlasenko, Nataliia; Gapon Svіtlana; Zhuk, Maryna; Dyachenko-Bohun, Marina; Hrytsai, Nataliia; Grygus, Igor (Ecological Questions, 2022)
The main representatives of meadow Poaceae and Fabaceae of Poltava region are established and their ecomorphic analysis is made 93 species of meadow Poaceae have been found in meadow phytocenoses, which are grouped into 44 genera. Among the found cereals on biomorphs are dominated by perennials (73.0%), on climamorphs among them approximately the same number of cryptophytes and hemicryptophytes, consideration of hygromorphs of the family indicates the predominance of mesophytic plants (56.0%), the bulk of species by tropomorphs belongs to mesotrophic (46.0%), viewing heliomorphs of identified family members indicates their photophobia. 71 species of Fabaceae belonging to 16 genera were found in the meadows. According to biomorphs, most of the identified species are perennials (73.0%). According to ecomorphs, mesophilic, light-loving species, which love soils of medium richness (more than half of all identified species), predominate among the studied species. The consequences of studying the protein in meadow Poaceae and Fabaceae of Poltava region are given. The total protein accumulation in the species studied by us was in the range of 2.5–25.8%. The average values for families are given and specific quantitative indicators of separate genera and species are given. The division of the studied species into three groups according to the content of the indicator is proposed: with low (up to 6.9%), medium (7.0-13.0%) and high (more than 13.0%) number. The studied species were analyzed on a scale of protein content (from 0 to 20 points). According to the given score, the studied cereals are in the group of species with low and medium content, and legumes - medium and high. In the dynamics of protein content during the phases of the growing season you can see a certain trend. Maximum protein is accumulated by representatives at earlier stages of ontogenesis. Analysis of the indicator, depending on their relationship to the biomorph showed some patterns. Thus, annual species, on average, contain an indicator at the level of the second group, and perennial - all three groups. Two-year-olds most often have protein at the level of the third group. This is understandable because they need a lot of nutrients for overwintering and active flowering and fruit formation next year. Moisture conditions also affect protein accumulation. Thus, the studied xerophilous Poaceae according to our research have 9.2 ± 0.4%, mesophilic - 8.2 ± 1.2%. Proven value biomorfy to quantify protein content. It is shown that the concentration parameter affecting growing conditions, including moisture.